Toll-Like Receptor 4 Deficiency Impairs Motor Coordination - Zhu, Jian-Wei; Li, Yi-Fei; Wang, Zhao-Tao; Jia, Wei-Qiang; Xu, Ru-Xiang (Frontiers in Neuroscience, 2016)
The cerebellum plays an essential role in balance and motor coordination. Purkinje cells (PCs) are the sole output neurons of the cerebellar cortex and are critical for the execution of its functions, including motor coordination. Toll-like receptor 4 (TLR) 4 is involved in the innate immune response and is abundantly expressed in the central nervous system; however, little is known about its role in cerebellum-related motor functions. To address this question, we evaluated motor behavior in TLR4 deficient mice. We found that TLR4−/− mice showed impaired motor coordination. Morphological analyses revealed that TLR4 deficiency was associated with a reduction in the thickness of the molecular layer of the cerebellum. TLR4 was highly expressed in PCs but not Bergmann glia, cerebellar granule cell; however, loss of TLR4 decreased the number of PCs. These findings suggest a novel role for TLR4 in cerebellum-related motor coordination through maintenance of the PCs population.